Performance of Unconventional Irrigation in New Aonla Tree Plantations in Sodic Black Soils. - R. K. Sharma; S.C. Tiwari; S.K.Verma; J. Singh (Journal of Soil and Water Conservation, 2022)
The Capital-intensive reclamation of sodic black soil calls for utilizing such untapped lands through sodic soils. The conventional irrigation method like surface sprinkler and drip are not effective in sodic black soils due to low infiltration and higher “percentage of dispersible clay. In order to evolve suitable low cost unconventional method of irrigation for establishing new tree plantation in sodic black soils, a study is planned to compare performance of the Proposed unconventional method with conventional check basin method in sodic black soils at Salinity Research Station, Barwaha during 2002-03. Study reveals that unconventional irrigation arrangement T, (pipe dia. 100 mm and length 40 cm) is observed markedly effective in performance as compared to conventional check basin method. There is a reduction in amount of irrigation water by 69% as compared to conventional check basin method in which 80 liters of irrigation water was applied per month per plant. Apart from saving of irrigation water the survival rate of new tree plantation was 100% as compared to 85% in check basin besides the improved growth in terms of plant height and thickness of collar diameter as 97.25 cm and 1.46cm, respectively than that of 90cm and 1.31 cm in check basin method. Finally present investigation insinuates that unconventional irrigation arrangement T, (The PVC pipe having 100 mm diameter 40 cm length. embedded30cmin soil with perforation facing to wards plantation) appears markedly effective and promising among various tried arrangements over check basin method in establishing new Aonla tree plantation.